Patient‐Reported Outcomes Predict Future Emergency Department Visits and Hospital Admissions in Patients With Stroke - Irene L. Katzan; Nicolas Thompson; Andrew Schuster; Dolora Wisco; Brittany Lapin (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Identification of stroke patients at increased risk of emergency department (ED) visits or hospital admissions allows implementation of mitigation strategies. We evaluated the ability of the Patient‐Reported Outcomes Information Measurement System (PROMIS) patient‐reported outcomes (PROs) collected as part of routine care to predict 1‐year emergency department (ED) visits and admissions when added to other readily available clinical variables. Methods and Results This was a cohort study of 1696 patients with ischemic stroke, intracerebral hemorrhage, subarachnoid hemorrhage, or transient ischemic attack seen in a cerebrovascular clinic from February 17, 2015, to June 11, 2018, who completed the following PROs at the visit: Patient Health Questionnaire‐9, Quality of Life in Neurological Disorders cognitive function, PROMIS Global Health, sleep disturbance, fatigue, anxiety, social role satisfaction, physical function, and pain interference. A series of logistic regression models was constructed to determine the ability of models that include PRO scores to predict 1‐year ED visits and all‐cause and unplanned admissions. In the 1 year following the PRO encounter date, 1046 ED visits occurred in 548 patients; 751 admissions occurred in 453 patients. All PROs were significantly associated with future ED visits and admissions except PROMIS sleep. Models predicting unplanned admissions had highest optimism‐corrected area under the curve (range, 0.684–0.724), followed by ED visits (range, 0.674–0.691) and then all‐cause admissions (range, 0.628–0.671). PROs measuring domains of mental health had stronger associations with ED visits; PROs measuring domains of physical health had stronger associations with admissions. Conclusions PROMIS scales improve the ability to predict ED visits and admissions in patients with stroke. The differences in model performance and the most influential PROs in the prediction models suggest differences in factors influencing future hospital admissions and ED visits.